Study the Effect of Epoxy Additives on Some Physical Properties of Asphalt Cement - SalimM.A. Al-ani; Thamer J. Ahmed; Khalil T. Al-Rawi; Taher M.A. Al-ani (مجلة جامعة الانبار للعلوم الصرفة, 2012)
Abstract:In the series of study on the asphalt cement to improve properties of asphalt cement several polymers materials are used for this purpose. In this study Epoxy used at different percentage by weight (1, 2, 4 and 6) %. Epoxy was added in three cases, pure Epoxy and the other two cases were mixing of Catalyst-Epoxy by weight in the two ratio (1:3) and (1:4).The effect of additives on the asphalt cement properties are evaluated by penetration test (ASTM D-5)(10), softening point test (ASTM D-2398)(10), and Kinematics viscosity test (ASTM D-2170)(10). Temperature susceptibility of asphalt cement was evaluated by using Penetration viscosity number ( PVN ). The study shows that Epoxy, 1:3 Epoxy and 1:4 Epoxy additives have more effect on the physical properties of asphalt cement and make asphalt softer than original asphalt cement, the additives reduced the temperature susceptibility, but Epoxy have more reduction in the susceptibility of asphalt cement compared with 1:3 Epoxy and 1:4.